Analysis of Islamic Criminal Law on Cases of Sexual Violence by Persons With Physical Disabilities (Case Study of Mataram District Court Decision No. 23/PID.SUS/2025/PN MTR) - Zaskia Herlia Ramadhani; Mohamad Sar’an; Yayan Muhamad Royani (Journal of Social Research, 2025)
Cases of sexual violence are crimes against humanity that not only physically injure the victim, but also cause deep psychological trauma. However, the phenomenon that occurred in Mataram in 2024 shows a different condition, where people with physical disabilities are actually perpetrators of sexual violence. This raises complex legal issues, especially related to the limits of criminal liability and the application of the principle of justice. This study aims to analyze the criminal liability of perpetrators with physical disabilities in cases of sexual violence based on the Mataram District Court Decision Number 23/Pid.Sus/2025/PN Mtr and review its relevance to the principles of Islamic criminal law. The method used is normative juridical with a case approach, through the study of primary legal sources in the form of the Qur'an, hadith, fiqh jinayah books, as well as laws and regulations such as Law Number 12 of 2022 concerning the Crime of Sexual Violence and Law Number 8 of 2016 concerning Persons with Disabilities. The results of the study show that in positive law, perpetrators with physical disabilities can obtain mitigating considerations, as reflected in Decision Number 23/Pid.Sus/2025/PN Mtr which imposes a lighter sentence than the prosecutor's demands. While in the perspective of Islamic criminal law, the measure of criminal liability is determined by reason (?aql) and moral awareness (ahliyyah al-ad?), not by physical conditions. Therefore, people with physical disabilities who have common sense are still seen as full mukallaf who are obliged to account for their actions. Acts of sexual violence in this context are classified as jarimah ta'z?r syadidah (heavy ta'zir), the sanctions of which can be increased according to the level of social and moral damage caused. This study emphasizes the importance of applying the principles of substantive justice and benefits in deciding cases involving perpetrators with disabilities, without removing the essence of criminal responsibility. These findings are expected to contribute to the development of inclusive and contextual Islamic criminal law on disability and sexual violence issues in Indonesia.